Comparative transcriptomics analysis of developing peanut (Arachis hypogaea L.) pods reveals candidate genes affecting peanut seed size - Wu, Yue; Sun, Ziqi; Qi, Feiyan; Tian, Mengdi; Wang, Juan; Zhao, Ruifang; Wang, Xiao; Wu, Xiaohui; Shi, Xinlong; Liu, Hongfei; Dong, Wenzhao; Huang, Bingyan; et al. (Frontiers in Plant Science, 2022)
Pod size is one of the most important agronomic features for peanut, which directly affects peanut yield. Studies on the regulation mechanism underpinning pod size in cultivated peanuts remain hitherto limited compared to model plant systems. To better understand the molecular elements that underpin peanut pod development, we conducted a comprehensive analysis of chronological transcriptomics during pod development in four peanut accessions with similar genetic backgrounds, but varying pod sizes. A number of plant transcription factors, phytohormones, and the mitogen-activated protein kinase (MAPK) signaling pathways were significantly enriched among differentially expressed genes (DEGs) at five consecutive developmental stages, revealing an eclectic range of candidate genes, including PNC, YUC, and IAA that regulate auxin synthesis and metabolism, CYCD and CYCU that regulate cell differentiation and proliferation, and GASA that regulates seed size and pod elongation via gibberellin pathway. It is plausible that MPK3 promotes integument cell division and regulates mitotic activity through phosphorylation, and the interactions between these genes form a network of molecular pathways that affect peanut pod size. Further, two variant sites, GCP4 and RPPL1, were identified which are stable at the QTL interval for seed size attributes and function in plant cell tissue microtubule nucleation. These findings may facilitate the identification of candidate genes that regulate pod size and impart yield improvement in cultivated peanuts.